Presencia y performance: los cantares mexicanos frente al historicismo - Charlie D. Hankin (E-Spania, 2018)
This paper rehearses a re-reading of the cantares mexicanos taking as a point of departure the hypothetical reconstruction of their performance. We analyze the cantares as sonoric objects that resist writing and metaphor. The cantares function through a relationship of metonymic proximity between words and things and is constantly constructed in the presence – both temporal and spatial – of the performance. Metonymy is expressed, moreover, through the ingestion of hallucinogenic flowers by the singer, through which emerges a bridge between visible and invisible worlds. Analyzing this “semiotics” through the orality and experience of the performance spectacle, we propose that the contares invite new ways of thinking about time alternative to the historicism that predominates in historiographic production in the West.